PENGARUH INFLASI, SUKU BUNGA, DAN NILAI TUKAR RUPIAH TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA - Siska Wahyuni Sukamto (Manajemen Bisnis, 2016)
This studi was conducted to determine the effect macro economic variable of inflation, interest rate, and exchange rate againts the stock price indeks on indonesia stock exchange, and look for variables that effect most dominant among the three variables in the stock price index. Type of research is quantitative research, using multiple regression analysis, F test, t test and standardized coefficient as a tool of analysis in this study. Results of the study found that the variables inflation, interest rate, and exchange rate either simultaneously is significant effect on stock price index. Either partially the inflation variable has a significant effect on stock price index, while the variable interest rate have a significant negative effect on the stock price index, and the exchange rate has a significant effect on the stock price index, inflation variable are the most dominany effect on stock price index on Indonesia Stock Exchange